Tudor Towns - Jessop,Joanne; Illustrated by Dennis, Peter (Hove Wayland Publishers, 1990)
A paperback edition of the title first published in 1990. Illustrated with colour photographs and artwork a title in the BEGINNING HISTORY series which looks at the richness and variety of life in Tudor towns, as well as the problems that people faced
Include Color Illustration and Index
Keywords: England -- Cities and towns